Influence of Sb doping on the structural, optical and electrical properties of p-ZnO thin films prepared on n-GaN/Al2O3 substrates by a simple CVD method. (January 2015) - Feng, Q.J.; Liu, S.; Liu, Y.; Zhao, H.F.; Lu, J.Y.; Tang, K.; Li, R.; Xu, K.; Guo, H.Y.
Abstract: ZnO thin films with different Sb doping concentrations were prepared on n-GaN/Al2 O3 substrates by simple chemical vapor deposition. Field-emission scanning electron microscopy (FE-SEM) showed that the morphologies of ZnO thin films were rougher and the size of the crystal grains reduced with increasing Sb concentration. The X-ray diffraction measurements indicated that the (002) diffraction peak positions of samples shifted gradually towards the lower angle side, which explained the substitution of Sb 3+ into the Zn site by Sb doping. In addition, Hall measurement results indicated that Sb doped ZnO thin films had p-type conductivity, and the optimal Sb2 O3 /ZnO mass ratio for p-type ZnO thin film was approximately 1:4. Optical absorption spectrum measurement indicated that the energy gaps of the samples were evidently narrowed with increasing Sb doping concentration.